Stratospheric aerosol—Observations, processes, and impact on climate. (7th May 2016) - Kremser, Stefanie; Thomason, Larry W.; von Hobe, Marc; Hermann, Markus; Deshler, Terry; Timmreck, Claudia; Toohey, Matthew; Stenke, Andrea; Schwarz, Joshua P.; Weigel, Ralf; Fueglistaler, Stephan; Prata, Fred J.; et al.
Abstract: Interest in stratospheric aerosol and its role in climate have increased over the last decade due to the observed increase in stratospheric aerosol since 2000 and the potential for changes in the sulfur cycle induced by climate change. This review provides an overview about the advances in stratospheric aerosol research since the last comprehensive assessment of stratospheric aerosol was published in 2006. A crucial development since 2006 is the substantial improvement in the agreement between in situ and space‐based inferences of stratospheric aerosol properties during volcanically quiescent periods. Furthermore, new measurement systems and techniques, both in situ and space based, have been developed for measuring physical aerosol properties with greater accuracy and for characterizing aerosol composition. However, these changes induce challenges to constructing a long‐term stratospheric aerosol climatology. Currently, changes in stratospheric aerosol levels less than 20% cannot be confidently quantified. The volcanic signals tend to mask any nonvolcanically driven change, making them difficult to understand. While the role of carbonyl sulfide as a substantial and relatively constant source of stratospheric sulfur has been confirmed by new observations and model simulations, large uncertainties remain with respect to the contribution from anthropogenic sulfur dioxide emissions. New evidence has been provided that stratospheric aerosol can also contain small amounts of nonsulfate matter such as black carbon and organics. Chemistry‐climate models have substantially increased in quantity and sophistication. In many models the implementation of stratospheric aerosol processes is coupled to radiation and/or stratospheric chemistry modules to account for relevant feedback processes. Key Points: First comprehensive review of stratospheric aerosol since 2006 Differences between in situ and space‐based inferences of stratospheric aerosol properties have been resolved Improved understanding of the role of minor volcanic eruptions and nonsulfate aerosols on the stratospheric aerosol layer has been achieved